Proton-Transfer and Photo-Deamination Reactive Mechanisms Studies of Amines Compounds (Communications in Computational Chemistry, 2017)
The reference [J. Org. Chem. 2015, 80, 10817.10828] has reported that theQuinone Methides (QMs) that are of significant medicinal benefits in biological fieldcan be generated via photo-deamination reaction. In this study, the density functionaltheory (DFT) and time-dependent DFT (TDDFT) methods have been carried out toinvestigate the reactive mechanisms of free amines compounds 1 and 3. The excitedstate hydrogen bonding strengthening mechanism has been demonstrated by analysesof frontier molecular orbitals (MOs). Potential energy surfaces (PESs) calculations havebeen performed for illustrating excited state intramolecular proton transfer (ESIPT) andphoto-deamination reactions of forms 1 and 3. The reactive sites of QM1 and QM3molecules can be accurately predicted via analyses of ESP.
Keywords: Photo-deamination reaction; Excited state intramolecular proton transfer; Potential energy surfaces; Hydrogen bond.